Using Artificial Intelligence in Arabic Learning: Opportunities and Challenges: استخدام الذكاء الاصطناعي في تعلم اللغة العربية: الفرص والتحديات - Azwir, Azwir; Zulkhairi, Zulkhairi; Zulhelmi, Zulhelmi; Yasir, Muhammad; Rahmi, Maulidatun (The Department of Arabic Language Education, Pascasarjana Universitas Islam Negeri Banda Aceh of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2024)
Artificial intelligence (AI) has emerged as a tool with great potential to change the way we teach and learn, especially in the context of language learning. This article discusses the various benefits and challenges associated with integrating AI into education. By leveraging AI technology, teachers can create more personalized and adaptive learning experiences, uniquely tailored to each student's needs and abilities. In addition, AI can enhance the effectiveness of learning by providing real-time feedback and automated assessments, helping students develop their speaking and writing skills. However, challenges such as data privacy and the need for clear policies must be addressed to ensure the effective and ethical application of AI-based tools. More systematic research and assessment is needed to understand the impact of AI on student learning outcomes and to build trust between teachers and other stakeholders.